Public Governance for Promoting the Pacu Jalur Cultural Event in Kuantan Singingi - Julianis; Entang Adhy Muhtar (Journal of Governance and Social Policy, 2025)
This study aims to analyze the role of public governance in promoting Pacu Jalur as an effort to increase the competitiveness of cultural tourism in Riau Province. The Pacu Jalur tradition, as a cultural heritage of the Kuantan Singingi community, has high historical and social value and has become an icon of regional cultural tourism. However, the management and promotion of this activity still face various obstacles, such as limited coordination between agencies, infrastructure support, and consistency in promotional programs. This study uses a descriptive qualitative approach with a literature study method, namely examining policy documents, government reports, and scientific literature related to governance and cultural tourism. The theory used in this study is collaborative governance by Ansell and Gash. The results of the study show that the principles of public governance that emphasize transparency, collaboration, and participation are an important basis for strengthening the promotion of Pacu Jalur. The active role of the local government together with the community is a major factor in maintaining the sustainability of activities and strengthening the cultural image of Riau at the national level.